COVID−19−induced anxiety, depression and stress among healthcare professionals in Sri Lanka - Lahiru Udayanga; Ayesha Perera; Lakchani Dissanayaka (Asian Pacific Journal of Tropical Medicine, 2022)
Objective: To assess the degree of anxiety, depression and stress due to the COVID-19 epidemic among healthcare professionals in Sri Lanka. Methods: Healthcare professionals from 6 selected government and private hospitals located in Gampaha District were recruited for the study. The socio-demographic factors, knowledge and attitudes of healthcare professionals on COVID-19 was collected through a self-administered questionnaire, while Depression, Anxiety and Stress Scale score was used to assess the psychological wellbeing. Descriptive statistics and binary logistic regression techniques were used for data analysis. Results: Totally 324 healthcare professionals were included and the respondents had a high overall level of knowledge towards COVID-19. Twenty-five percent of the respondents had different levels of anxiety, while 10.8% had mild depression, and 4.6% had moderate depression. Interestingly, 40.4% of the respondents had mild stress, and 11.1% had moderate stress. Young people (20-35 years), medical laboratory technologist and nursing officer, being quarantined, having a SARS-CoV-2-infected family member, involvement in COVID-19 patient care, and limited availability of personal protection equipment, were recognized as significant risk factors associated with anxiety, depression and stress. Conclusions: The healthcare professionals are high-risk groups to experience psychological impacts from COVID-19. Continuous monitoring and implementing appropriate intervention activities and provision of counseling support are highly recommended.